Comparative Fishing Ability and Economic Efficiency of Mechanised Trawlers Operating Along the Kerala Coast - IYER, H. KRISHNA; RAJENDRAN, R.; CHOUDHURY, R. L. ROY (Fishery Technology, 1968)
This study was undertaken with a view to finding out thecomparative fishing ability and economic performance of differentfishing vessel sizes 9.15 m (30'), 9.76 m (32') and 10.97 m (36')designed by the Central Institute of Fisheries Technology andoperating along the Kerala coast. Data were collected from selectedvessels of these sizes for four consecutive fishing seasons from1964-65 to 1967-68. The catch / unit effort and total effort per yearfor the 10.97 m (36') vessels were much better than those for the9.76m (32') vessels. The yearly landings and the crew remunerationfor the former were about twice those of the 9.76 m (32') vessels.The economic efficiency of the 10.97 m (36') vessels was also muchbetter. The decline in landings per year in both size groups wasmore due to the reduction in the effort per year than the decline incatch / unit effort.